PENGATURAN KECEPATAN KIPAS ANGIN DENGAN TEKNOLOGI INVERTER - M. Taufiq Tamam; Arif Johar Taufiq (Universitas Muhammadiyah Purwokerto, 2012)
This study aims to create a tool, that is inverter which can be used to adjust the fan rotation speed. The research was carried out using variable astable multivibrator circuit as a switching circuit on the inverter.After testing, the magnitude of the fan rotation speed depending on the size of the resulting frequency of astable multivibrator. Key word: inverter, astable multivibrator, fan.